2020
DOI: 10.3389/fgene.2020.564301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Circular RNA Expression Patterns and MicroRNA Interaction Networks in Mesial Temporal Lobe Epilepsy

Abstract: Circular RNAs (circRNAs) regulate mRNA translation by binding to microRNAs (miRNAs), and their expression is altered in diverse disorders, including cancer, cardiovascular disease, and Parkinson's disease. Here, we compare circRNA expression patterns in the temporal cortex and hippocampus of patients with pharmacoresistant mesial temporal lobe epilepsy (MTLE) and healthy controls. Nine circRNAs showed significant differential expression, including circRNA-HOMER1, which is expressed in synapses. Further, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 52 publications
2
23
1
Order By: Relevance
“…We validated the upregulation of circ_Arhgap4 and circ_Nav3 at the DOFS and found similar regulation of their circular and linear host transcripts. This is in contrast with earlier findings, in which no obvious correlation was observed between specific circRNAs and the expression of their parental genes in mTLE ( Gray et al, 2020 ). A positive correlation in the expression of circRNA and mRNA species suggests that the RNA changes are a consequence of transcriptional activation of these genes rather than an alteration of splicing events that lead to circRNA formation ( Jeck and Sharpless, 2014 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We validated the upregulation of circ_Arhgap4 and circ_Nav3 at the DOFS and found similar regulation of their circular and linear host transcripts. This is in contrast with earlier findings, in which no obvious correlation was observed between specific circRNAs and the expression of their parental genes in mTLE ( Gray et al, 2020 ). A positive correlation in the expression of circRNA and mRNA species suggests that the RNA changes are a consequence of transcriptional activation of these genes rather than an alteration of splicing events that lead to circRNA formation ( Jeck and Sharpless, 2014 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Over the past years, a plethora of studies has shown that ncRNAs can influence various processes in the nervous system, including neuronal development, apoptosis, neurogenesis, oxidative stress, synaptic plasticity, and immune system activation, that are disturbed in the pathological process leading to mTLE ( Henshall and Kobow, 2015 ; Henshall et al, 2016 ; Shao and Chen, 2017 ; Villa et al, 2019 ; Mills et al, 2020 ). In addition, experimental evidence highlights defects in post-transcriptional regulation in mTLE and the expression and function of different classes of ncRNAs is perturbed in experimental TLE and in TLE patients ( Van Gassen et al, 2008 ; Jimenez-Mateos et al, 2012 ; Kan et al, 2012 ; Gong et al, 2018 ; Lee et al, 2018 ; Li J. et al, 2018 ; Guelfi et al, 2019 ; Fu et al, 2020 ; Gray et al, 2020 ; Venø et al, 2020 ). Together, these observations support the idea that ncRNAs may participate in the process of epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, independent expression regulation has also been observed ( Jeck et al, 2013 ; Salzman et al, 2013 ; Ashwal-Fluss et al, 2014 ; Rybak-Wolf et al, 2014 ; Xu et al, 2018 ). Our findings are in line with previous work showing no clear correlation between a set of mTLE-associated circRNAs and linear transcripts from the same loci ( Gray et al, 2020 ). These observations suggest that changes in for example back-splicing rather than transcriptional activation of the SATB1 locus may cause altered circ_Satb1 expression in the hippocampus of mTLE patients.…”
Section: Discussionsupporting
confidence: 94%
“…Unfortunately, their specific neuronal functions remain poorly understood. Our own work and that of others shows deregulated expression of circRNAs in mTLE patients and in experimental models of epilepsy (e.g., Gong et al, 2018 ; Lee et al, 2018 ; Li et al, 2018 ; Gray et al, 2020 ; Gomes-Duarte et al, 2021 ). For example, we have recently reported enrichment of circRNA deregulation at the transition to recurrent spontaneous seizures ( Gomes-Duarte et al, 2021 ).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation